2010
DOI: 10.1149/1.3464775
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of Oxygen and Nitric Oxide at Low Temperature on La[sub 1−x]Sr[sub x]CoO[sub 3−δ] Cathodes

K. Kammer Hansen

Abstract: Six La1−xSrxCoO3−δ (x=0,0.05,0.15,0.25,0.35,0.50) perovskites were synthesized and characterized by powder X-ray diffraction and cyclic voltammetry on conical electrodes in either air or nitric oxide in argon at 200, 300, and 400°C . At 200°C , the current densities in air was the highest for the strontium-free cobaltite, whereas the current densities were the highest for La0.95Sr0.05CoO3−δ in the nitric oxide-containing atmosphere. This was also the compound with the highest INO/InormalO2 current ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The magnitude of current densities for the LSCrV perovskites can be compared with the magnitude of the current densities obtained for strontium substituted lanthanum cobaltite's (LSCo) under the same conditions as used in this study. 20 The magnitude of the current densities is of the same order of magnitude at 200 and 300 • C. At 400 • C the magnitude of the current densities is similar for low strontium substituted lanthanum cobaltite's, but the magnitude of the current density for the most active LSCo perovskite La 0.5 Sr 0.5 CoO 3-δ are many times higher than for the LSCrV compounds. This is probably due to a high oxide ionic conductivity of the La 0.5 Sr 0.5 CoO 3-δ compound at 400 • C compared to the other compounds.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The magnitude of current densities for the LSCrV perovskites can be compared with the magnitude of the current densities obtained for strontium substituted lanthanum cobaltite's (LSCo) under the same conditions as used in this study. 20 The magnitude of the current densities is of the same order of magnitude at 200 and 300 • C. At 400 • C the magnitude of the current densities is similar for low strontium substituted lanthanum cobaltite's, but the magnitude of the current density for the most active LSCo perovskite La 0.5 Sr 0.5 CoO 3-δ are many times higher than for the LSCrV compounds. This is probably due to a high oxide ionic conductivity of the La 0.5 Sr 0.5 CoO 3-δ compound at 400 • C compared to the other compounds.…”
Section: Discussionmentioning
confidence: 84%
“…For manganite and ferrite based perovskites it has been shown that the properties needed to reduce nitric oxide is due to the amount of a trivalent transition metal ion and the amount of oxygen vacancies, whereas for the cobaltite's the same is probably valid, but with the exception that also the mobility of the oxygen ions is important for the cobaltite's with a high amount of strontium doping. 20,24,25 In the case of the chromites it seems like that the role of the trivalent transition metal cation is less important, and that the electronic conductivity and the amount of oxygen vacancies are the most important properties. The reason for this difference could be that Cr is less catalytic active for the reduction of nitric oxide than the three other transition metal ions.…”
Section: Discussionmentioning
confidence: 99%
“…The perovskite-type cubic oxide (ABO 3 ; A = La, Ba, Sr; B = Co, Fe, Al, Mg; O-oxygen) based systems have generated immense interest due to their potential applications as gas separation membranes, solid electrolyte materials, and catalysts besides in fuel cells, sensors, etc [1][2][3][4][5][6][7][8][9][10]. Their membranes possess a unique capacity of oxygen separation from the air and so play a vital role in industry and power generation [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%